2016
DOI: 10.1002/jmri.25447
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hippocampal substructures in focal temporal lobe epilepsy with and without hippocampal sclerosis at 7T

Abstract: ACKNOWLEDGMENTSWe would like to acknowledge Joe Gati and Trevor Szekeres for development and testing of the 7T MRI protocols. GRANT SUPPORTThis work was supported by grants from CIHR (MOP 184807) and NSERC. RUNNING TITLE:Hippocampal sub-structures at 7T. ABSTRACTPurpose: To provide a more detailed investigation of hippocampal subfields using ultrahigh field magnetic resonance imaging (MRI) for the identification of hippocampal pathologies in temporal lobe epilepsy. Materials and Methods:Patients (N=13) with dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…Previous work has shown that volume loss in selective hippocampal subfields is correlated to epilepsy. [39][40][41] It has been shown that different parts of the hippocampus show different levels of resistance to disruption in perfusion, with the CA1 region known to be particularly sensitive, whereas CA2 and CA3 are thought to be particularly resistant. 42 Thus, it may be possible that this change in VD is also associated with particular hippocampal subfields.…”
Section: Additional Limitations and Future Directionsmentioning
confidence: 99%
“…Previous work has shown that volume loss in selective hippocampal subfields is correlated to epilepsy. [39][40][41] It has been shown that different parts of the hippocampus show different levels of resistance to disruption in perfusion, with the CA1 region known to be particularly sensitive, whereas CA2 and CA3 are thought to be particularly resistant. 42 Thus, it may be possible that this change in VD is also associated with particular hippocampal subfields.…”
Section: Additional Limitations and Future Directionsmentioning
confidence: 99%
“…The hippocampus is implicated in many neurological diseases including Alzheimer's disease (AD), epilepsy, and schizophrenia, among others (Barnes et al, 2009;Bernasconi, Natsume, & Bernasconi, 2005;Goubran et al, 2016;Santyr et al, 2017;Steen, Mull, McClure, Hamer, & Lieberman, 2006). Hippocampal volumetry has been found to be a critical biomarker of aging and dementia (Courchesne et al, 2000;Jack Jr et al, 1998).…”
mentioning
confidence: 99%
“…The key advantage of PMC in this setting is that we can achieve high SNR using averaging of scans with clinically tractable scan durations without the need for image registration, which can be difficult for slabs with limited coverage and can introduce blurring. Our rater analysis demonstrates that PMC with this system provides significantly improved overall image quality (ie, reduced motion artifact) and allows for better visualization of clinically important structures: the gray–white junction (focal cortical dysplasias), the deep gray nuclei (movement disorders), and the hippocampus (neurodegenerative diseases, epilepsy, and mild traumatic brain injury). The effect of motion correction is seen in healthy, compliant subjects with minimal motion, but a larger improvement is seen in the context of larger magnitude motion.…”
Section: Discussionmentioning
confidence: 94%